2010
DOI: 10.1063/1.3506697
|View full text |Cite
|
Sign up to set email alerts
|

Optical studies of degradation of AlGaN quantum well based deep ultraviolet light emitting diodes

Abstract: Articles you may be interested inHigh current-induced degradation of AlGaN ultraviolet light emitting diodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…Some of them extend for a few lm, thus, they might contain dislocation clusters rather than individual defects. 16 However, such lower intensity spots do not appear in all scans. Thus, dislocations alone cannot account for areas with an increased rate of the nonradiative recombination.…”
Section: Resultsmentioning
confidence: 96%
“…Some of them extend for a few lm, thus, they might contain dislocation clusters rather than individual defects. 16 However, such lower intensity spots do not appear in all scans. Thus, dislocations alone cannot account for areas with an increased rate of the nonradiative recombination.…”
Section: Resultsmentioning
confidence: 96%
“…Nitrogen vacancies V N , [11,14,[17][18][19]] sites of out-diffused Al, [11][12][13] and oxides of Al or Ga [11,20- The study of the photomodification is of special interest in view of the development of AlGaN-based UV LDs and high-power FETs, since high injected carrier densities are typical for these devices.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that an increase in leakage current could signify an increase in non-radiative states that are created when electrons aggressively make it through the quantum wells and electron block into the p-type cladding layer. 10 What is unknown is in the voltage range of the secondary slope (3-4 V) why the increase in current at time zero is so much more than after aged conditions. This type of degradation monitoring by laser spotting is still in a preliminary stage and must be further developed.…”
Section: Stress Conditions and Changes Over Timementioning
confidence: 99%
“…Recent studies of UV LED degradation have identified a discrepancy between PL and EL measurements. 5,9,10 The degradation in PL (which targets the quantum wells) is either negligible or significantly less than the orders of magnitude decrease in photon counts encountered in the EL measurements. This suggests that the degradation is not occurring in the active region but more likely in the p-type cladding material increasing the number of nitrogen vacancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation